The Role of The Community in Planting Social Children's Social Values in The Shock of Youth Children's Social Behavior of Soki Village, Belo Sub-District, Bima Regency, West Nusa Tenggara - Astuti, Astuti; Prajanti, Sucihatiningsih Dian Wisika; Atmaja, Hamdan Tri (JESS (Journal of Educational Social Studies), 2018)
The influence of information technology influence on the development of social and cultural values ​​maja labo dahu (fear and shame) in young children. The purpose of this research was to assess the role of families and schools in instilling the values ​​of Social Culture on the social behavior of teenagers in the village of Soki, Belo subdistrict, Bima, West Nusa Tenggara. The method used is qualitative. Informants in this research is a family, a teacher at the school, teens, and communities. The technique of collecting data through observation, interview, and documentation. The validity of the data in this research using the technique of triangulation, triangulation method, and triangulation theory. The research result menunjuhkan role of the family in instilling the values ​​of diverse social and cultural forms, there are families who just instilling the values ​​of social and cultural limited to providing advice and does not give an example of good behavior, close supervision and not impose penalties if a child violates the values ​​that exist in society, the role of schools in imparting social values ​​culturally diverse, they instill social values ​​through the culture of the classroom learning activities. Public role in instilling social values ​​of culture in young children there is a declining trend in giving sanction to the adolescent who commits an offense priceless-owned social-cultural values ​​in society. The role of schools in imparting social values ​​culturally diverse, they instill social values ​​through the culture of the classroom learning activities. Public role in instilling social values ​​of culture in young children there is a declining trend in giving sanction to the adolescent who commits an offense priceless-owned social-cultural values ​​in society. The role of schools in imparting social values ​​culturally diverse, they instill social values ​​through the culture of the classroom learning activities. Public role in instilling social values ​​of culture in young children there is a declining trend in giving sanction to the adolescent who commits an offense priceless-owned social-cultural values ​​in society.